(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Metallized plastics with a decorative coating can withstand steel balls on the surface, and the impact area is not as deep even when the balls are thrown from above. And in light alloy products with the same coating, it is deeper. The corrosion resistance of metal-coated plastics is stronger than that of similarly coated metal parts. The reason for this is that plastic does not participate in the formation of galvanic microevaporation, and the hole formed by corrosion does not deepen, but only expands. When metal-coated plastics are used in atmospheric conditions, the appearance of the product is preserved for 2-3.5 years.